The Use of the Bible al School: A Challenge Both for Families and Schools - Delgado Gómez, Alfredo (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2020)
This paper aims to reflect upon the use of the Bible at school, what implies a challenge due to the spread of secularization. first, the obstacles that educators meet when using the Bible-some of them beyond the school context-are analysed. Secondly, it is reflected upon what the Bible really is, so that we don’t demand what the Bible cannot offer. Thirdly, some basic tips are outlined for using the Bible in today’s classroom. finally, it is presented a series of tasks and possibilities to put the Bible in the hands of both students and teachers as a fundamental tool for our faith and lives.